By-Laws and Ordinances of the City of Pittsburgh 28-29 (1828) - (:unkn) unknown (My University, 1774)
Ch. 703, § 1 : Prohibited on any thirty-first day of December, or first or second day of January, in every year, wantonly, and without reasonable occasion, discharge and fire off any hand-gun, pistol or other fire-arms, or shall cast, throw or fire any squibs, rockets or other fire-works, within the inhabited parts of this province, to the disturbance of any of his majesty’s subjects there inhabiting and being
Keywords: DISCHARGE